2013
DOI: 10.1017/s0007114512005454
|View full text |Cite
|
Sign up to set email alerts
|

Flavanone metabolites decrease monocyte adhesion to TNF-α-activated endothelial cells by modulating expression of atherosclerosis-related genes

Abstract: Flavanones are found specifically and abundantly in citrus fruits. Their beneficial effect on vascular function is well documented. However, little is known about their cellular and molecular mechanisms of action in vascular cells. The goal of the present study was to identify the impact of flavanone metabolites on endothelial cells and decipher the underlying molecular mechanisms of action. We investigated the impact of naringenin and hesperetin metabolites at 0·5, 2 and 10 mM on monocyte adhesion to TNF-a-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…The levels of circulating Ang II were significantly reduced, which otherwise leads to vasoconstriction. Flavanones can also modulate inflammatory process in atherosclerosis by reducing the binding of monocytes treated with Naringenin and Hesperitin, flavanones found primarily in citrus fruits, to TNFα activated endothelial cells [215]. …”
Section: Functional Foods Rich In Polyphenolsmentioning
confidence: 99%
“…The levels of circulating Ang II were significantly reduced, which otherwise leads to vasoconstriction. Flavanones can also modulate inflammatory process in atherosclerosis by reducing the binding of monocytes treated with Naringenin and Hesperitin, flavanones found primarily in citrus fruits, to TNFα activated endothelial cells [215]. …”
Section: Functional Foods Rich In Polyphenolsmentioning
confidence: 99%
“…In vitro , polyphenols impact the expression of genes in various cell types. It has been demonstrated that flavanone metabolites at physiological concentrations can modulate the expression of genes involved in inflammation in tumor necrosis factor (TNF)-α-stimulated human umbilical vein endothelial cells (HUVECs) [8]. Exposure of human monocytes to green tea polyphenols affected the expression of genes related to atherosclerosis development, such as CD36 , LXR-α , MYC or LDL-R [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the role of naringenin and its phase II metabolites on macrophage cholesterol intake and potential of foam cell formation (Chanet et al, 2013), the expression of the scavenger receptor CD36, a multiligand scavenger receptor responsible for the recognition and internalisation of oxidatively modified LDL, was evaluated. This gene was downregulated in untreated M1 cells -naringenin and its 7-glucuronide were able to significantly counteract this downregulation.…”
Section: Cd36mentioning
confidence: 99%
“…Several studies have reported an active role of various polyphenols within in vitro macrophage models Hämäläinen et al, 2007;Raso et al, 2001;Tsai et al, 1999), and recently, naringenin was also evaluated in macrophage/monocyte cultures, suggesting a role in the inhibition of inflammatory and atherosclerosis-related pathways (Chanet et al, 2013;Chao et al, 2010;Vafeiadou et al, 2009). Despite this interest in understanding the effect that phenolic substances could elicit on macrophages, specific molecular actions as well as the role of metabolites instead of parent plant compounds require further elucidation (Del Rio et al, 2013).…”
Section: Introductionmentioning
confidence: 99%